Greenhouse Gas Emissions from Hydropower Reservoirs - Kumar, Amit; Sharma, M.P. (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Hydropower reservoirs are found to emit about 35-70 times less greenhouse gas (GHG) compared to thermal power plants. The emissions not only depend on the type of eco-region in which the reservoir is located but also on the reservoir characteristics and water quality parameters. This paper reports the results of the impact of reservoir parameters and water quality characteristics on GHG emission from tropical, temperate and boreal reservoirs. For this purpose, linear equations are developed but the regression coeffi cient is found very poor. The R2 range for CO2 is 5×10-5 to 0.36 for tropical, temperate and boreal reservoirs and the R24 is 0.004- 0.244 respectively, which is far lower than 0.90, and cannot be accurately used for prediction. Thereafter, empirical regression equations are developed to see the combined impact of reservoir parameters and R2 is found as 0.48 for CO2 and 0.16 for CH4 for tropical, 0.34 and 0.37 for CO2 and CH4 respectively for temperate and 0.51 and 0.26 for boreal reservoirs. The R2 0.90 indicates that these equations cannot be used to accurately predict the emissions, but can be used to get some idea about emissions from the reservoirs. DOI: http://dx.doi.org/10.3126/hn.v11i0.7159 Hydro Nepal Vol.11 2011 pp.37-42